Evaluasi Implementasi Program Sistem Informasi Terpadu Penduduk Nonpermanen (SINTEN) di Kota Surakarta - Gaza Daffa Redfada; Wahyu Nurharjadmo (Jurnal Mahasiswa Wacana Publik, 2021)
This study aims to evaluate the implementation program and find what factors that influence the implementation of the SINTEN program. The research location is in Surakarta city, especially in the Population and Civil Registration Agency of Surakarta. The method used is qualitative descriptive, with sources based on interviews, observations, literature study, and documentation study with purposive informant determining technic. The data analysis technique was analyzed using Interactive Analysis Model by Miles and Huberman, and the method of data validity used is source triangulation and triangulation technic. The results showed that the implementation of the SINTEN program was carried out in three stages, namely the organizing stage, the interpretation stage, and the application or application stage with several forms of activity. Then these stages are seen from the aspect of program implementer compliance with technical instructions or implementation rules in Minister of Home Affairs Regulation Number 14 of 2015 showed in the organizing stage that the program implementers are not fully compliant and obedient to implementation rules, but in the interpretation stage and the application or application stage, which is carried out by the program implementer, it has been in accordance with and complience with the rules for implementing the program. Then the factors that became obstacles in the implementation of the SINTEN program were communication factors that existed both between program implementers and program targets that were less than optimal and less comprehensive, as well as resource factors that is budget resources that did not exist specifically for SINTEN programs and facilities resources which still need to be improved and developed in the implementation of the SINTEN program.